Intermediates in monensin biosynthesis: A late step in biosynthesis of the polyether ionophore monensin is crucial for the integrity of cation binding - Hüttel, Wolfgang; Spencer, Jonathan B.; Leadlay, Peter F. (Beilstein Journal of Organic Chemistry, 2014)
Polyether antibiotics such as monensin are biosynthesised via a cascade of directed ring expansions operating on a putative polyepoxide precursor. The resulting structures containing fused cyclic ethers and a lipophilic backbone can form strong ionophoric complexes with certain metal cations. In this work, we demonstrate for monensin biosynthesis that, as well as ether formation, a late-stage hydroxylation step is crucial for the correct formation of the sodium monensin complex. We have investigated the last two steps in monensin biosynthesis, namely hydroxylation catalysed by the P450 monooxygenase MonD and O-methylation catalysed by the methyl-transferase MonE. The corresponding genes were deleted in-frame in a monensin-overproducing strain of Streptomyces cinnamonensis. The mutants produced the expected monensin derivatives in excellent yields (ΔmonD: 1.13 g L−1 dehydroxymonensin; ΔmonE: 0.50 g L−1 demethylmonensin; and double mutant ΔmonDΔmonE: 0.34 g L−1 dehydroxydemethylmonensin). Single crystals were obtained from purified fractions of dehydroxymonensin and demethylmonensin. X-ray structure analysis revealed that the conformation of sodium dimethylmonensin is very similar to that of sodium monensin. In contrast, the coordination of the sodium ion is significantly different in the sodium dehydroxymonensin complex. This shows that the final constitution of the sodium monensin complex requires this tailoring step as well as polyether formation.
Keywords: antibiotics; biosynthesis; natural products; polyketides; Streptomyces; synthetic biology